The effectiveness of tax incentives to encourage private savings. Issue 2 (3rd July 2022) - Fadejeva, Ludmila; Tkacevs, Olegs
ABSTRACT: This study examines the impact of tax incentives for long-term savings on total private savings using data for Latvia contained in HFCS 2014 and 2017. The survey shows that contributions to tax-favoured savings plans are not associated with lower consumer spending and therefore do not contribute to an increase in private savings. Instead, these savings are achieved by lowering other, non-tax-favoured savings. This substitution effect on non-tax-favoured savings remains statistically significant even when excluding households with very low consumption levels and the ones whose reference person is relatively young/old and with a low level of education. However, the observed effect is not significant at the very bottom of the distribution of non-tax-favoured savings. The results of this study raise concerns that without additional measures to encourage retirement savings, particularly in the lower segment of the savings distribution, income inequality among retirees will continue rising.